THEORETICAL REVIEW AND LITERATURE ANALYSIS OF THE ROLE OF THE ENVIRONMENT IN HEALTH TOURISM - Jevtić, Miljana; Gajić, Tamara; Vukolić, Dragan (The Business of Tourism, 2024)
Abstract This paper presents a theoretical review and literature analysis on the role of the environment in health tourism. It examines key environmental factors such as air and water quality, biodiversity, climatic and geographical characteristics, and their impact on the development of health tourism destinations. Additionally, the paper explores how the preservation of natural resources and the implementation of sustainable practices in the tourism sector can contribute to the long-term sustainability of health destinations. Beyond environmental aspects, the paper also analyzes the socio-economic and cultural impacts of health tourism on local communities and regional development. Through a comprehensive review of existing literature, this paper provides a theoretical framework for future research and the development of strategies that enhance the synergy between environmental protection and health tourism.